Pengaruh Dukungan Suami terhadap Tingkat Kecemasan Ibu Hamil Trimester III dalam Menghadapi Persalinan - Andi Dwi Wahyuni; Siti Maimunah; Sofa Amalia (Universitas Muhammadiyah Jember, 2021)
of happiness as well as anxiety are inevitable events, almost all pregnant women are overshadowed by anxiety, and part of a process of reasonable adjustment to psychological changes that occur during pregnancy. Therefore, support from a husband is needed by pregnant women especially when they are in their third trimester of pregnancy which is nearing the time of delivery in order to reduce excessive anxiety during pregnancy. This study aims to determine the effect of husband's support on the anxiety level of third trimester pregnant women in Muhammadiyah Hospital, Malang City. The method in this study uses quantitative methods with data collection techniques in the form of purposive sampling. The method in data analysis uses simple linear regression. The subjects in this study were as many as 100 pregnant women who entered the third trimester of pregnancy at Muhammadiyah Hospital Malang. The analysis technique used is simple linear regression with the help of SPSS for Windows 10. Based on the results of the study there is an influence of husband's support on the anxiety level of third trimester pregnant women in facing childbirth.